2021
DOI: 10.3389/fimmu.2021.708670
|View full text |Cite
|
Sign up to set email alerts
|

An Early Myelosuppression in the Acute Mouse Sepsis Is Partly Outcome-Dependent

Abstract: Adult hematopoietic stem and progenitor cells (HSPCs) respond to bacterial infections by expansion to myeloid cells. Sepsis impairs this process by suppressing differentiation of stem cells subsequently contributing to an ineffective immune response. Whether the magnitude of HSPCs impairment in sepsis is severity-dependent remains unknown. This study investigated dynamics of the HSPC immune-inflammatory response in the bone marrow, splenic, and blood compartments in moribund and surviving septic mice. The 12-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Sepsis is a serious, life-threatening syndrome that is one of the leading causes of death in hospitals. 1 , 2 Sepsis was also among the leading causes of the death associated with COVID-19. 3 Despite significant advances in critical care, sepsis still has a relatively high short-term mortality rate due to organ failure due to a dysregulated response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a serious, life-threatening syndrome that is one of the leading causes of death in hospitals. 1 , 2 Sepsis was also among the leading causes of the death associated with COVID-19. 3 Despite significant advances in critical care, sepsis still has a relatively high short-term mortality rate due to organ failure due to a dysregulated response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental models of sepsis in wild-type and humanized mice were used to investigate changes in the hematopoietic compartment (3,4). These studies have identified that increased Notch-1 and IL-6 signaling in the bone marrow contributes to impaired hematopoiesis (5). Interestingly, the IL-6 level in the bone marrow milieu was increased only in mice with the most severe sepsis.…”
Section: Progenitor and Stem Cells In Sepsismentioning
confidence: 99%
“…In models of sepsis, including cecal ligation and puncture (CLP), fecal slurry models, or endotoxemia, rapid production of myeloid cells and selective expansion of myeloid-biased progenitors have been observed ( Scumpia et al., 2010 ) and are associated with survival ( Cuenca et al., 2015 ). Phenotypic HSPCs are reduced in the bone marrow (BM) during acute disease ( Darden et al., 2021 ; Morales-Mantilla et al., 2022 ; Skirecki et al., 2015 ; 2021 ), in part due to their mobilization and/or rapid differentiation, highlighting the profound requirement and consumption of innate immune cells during sepsis. However, even months after surviving acute sepsis, mice contain an expanded pool of granulocyte-monocyte progenitor cells (MPP GM s), suggesting sustained myelopoiesis post-sepsis ( Bomans et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%